2020
DOI: 10.1097/jcma.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with preterm labor, with special emphasis on preterm premature rupture of membranes and severe preterm labor

Abstract: Background: Preterm labor (PTL) can lead to preterm birth, which can cause neonatal mortality and morbidity. Preterm premature rupture of membranes (PPROM) and severe PTL (SPTL) are serious PTL subtypes. Hereby, we aimed to investigate risk factors associated with PPROM and SPTL, among Egyptian women. Methods: In this case-control study, 117 women were enrolled without any known medical risk for PTL. The control group (n = 45) had term labor (≥37 gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
8
0
4
Order By: Relevance
“…Also Maryuni and Kurniasih (14) found that mothers < 20 years and > 35 years were 2.6 times at risk of PPROM. Hosny et al (15) concluded that women below the age of 20 years were at high risk of PPROM. A study done by Linehan et al (16) found that the highest incidence of PROM was in the 18-35-years old group (74.6%) versus 73.2% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Also Maryuni and Kurniasih (14) found that mothers < 20 years and > 35 years were 2.6 times at risk of PPROM. Hosny et al (15) concluded that women below the age of 20 years were at high risk of PPROM. A study done by Linehan et al (16) found that the highest incidence of PROM was in the 18-35-years old group (74.6%) versus 73.2% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…pPROM is one of the main causes of neonatal mortality and morbidity, the main risk factors of this gyneco-obstetric pathology are related to the infection (Hosny et al 2019). Fetal membranes express innate immunity receptors that recognize the molecular patterns of pathogenic microorganisms such as LPS of E. coli, which results in a proinflammatory response as a part of a defense mechanism against the immunological challenge ( Abrahams et al 2004;Motedayyen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal age (<18 years, or >40 years), ethnicity (Black race), body mass index (<19 kg/m 2 ), smoking, stress (depression, anxiety), heavy physical labor, education, poverty, and other social factors have all been reported to be associated with sPTL. 34,35 The intrinsic factors like maternal genetic variations, immune response, obstetric factors (such as prior preterm delivery, uterine curettage, cervical factors, multiple gestations, and adverse outcome of previous term pregnancy 33 ) may also increase the risk of sPTL. Moreover, some diseases or disorders during pregnancy, such as kidney dysfunction, 36 renovascular disease, 37 cesarean section at term, 38 history of surgery for endometriosis 39 or cervical intraepithelial neoplasia, 40 were all associated with an increased risk of sPTL.…”
Section: Maternal Risk Factorsmentioning
confidence: 99%
“…Maternal age (<18 years, or >40 years), ethnicity (Black race), body mass index (<19 kg/m 2 ), smoking, stress (depression, anxiety), heavy physical labor, education, poverty, and other social factors have all been reported to be associated with sPTL 34,35 . The intrinsic factors like maternal genetic variations, immune response, obstetric factors (such as prior preterm delivery, uterine curettage, cervical factors, multiple gestations, and adverse outcome of previous term pregnancy 33 ) may also increase the risk of sPTL.…”
Section: Internal Risk Factors Affecting Preterm Labormentioning
confidence: 99%